2015
DOI: 10.4172/2155-952x.1000210
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Vein Endothelial Cells Migration in Matrigel by the Concentration Gradient of Vascular Endothelial Growth Factor

Abstract: Vascular endothelial growth factor (VEGF) has an ability to induce the migration of human umbilical vein endothelial cells (HUVEC). The objective of this study is to prepare several patterns of gelatin hydrogels for VEGF release and evaluate the 3-dimensional pattern of HUVEC migration in Matrigel by VEGF release. VEGF was incorporated into the gelatin hydrogel sheet to achieve the sustained release and generate the concentration gradient of VEGF. When Matrigel was put on the gelatin hydrogel sheet incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The dependency of cell migration to the VEGF content of the scaffolds was also studied by Obi et al [55]. They incorporated VEGF into a gelatin hydrogel sheet and put Matrigel seeded with HUVECs on these gelatin surfaces.…”
Section: Cell Migrationmentioning
confidence: 97%
“…The dependency of cell migration to the VEGF content of the scaffolds was also studied by Obi et al [55]. They incorporated VEGF into a gelatin hydrogel sheet and put Matrigel seeded with HUVECs on these gelatin surfaces.…”
Section: Cell Migrationmentioning
confidence: 97%
“…It is largely bound to glycosaminoglycans in vivo and released in response to need. Its angiogenic potential has been assessed in many in vitro studies such as cell migration assays using matrigel [8], collagen gels [9] and transwell migration assays [10]. It has also been evaluated in the CAM assay [11 14] as well as in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it had already been shown that endothelial cells, cultured in a proper matrix such as Matrigel, migrate in the direction of VEGF release. Accordingly, the gradient concentration of VEGF, formed in Matrigel, induces the migration of endothelial cell 42 …”
Section: Discussionmentioning
confidence: 99%